Determinantes macroeconómicos de los flujos migratorios ecuatorianos hacia Estados Unidos, periodo 1990 – 2020. - Vizuete Guadalupe, Jervis Hubet (2023)
Migration theories help to explain this phenomenon in a descriptive way. In the case of Ecuador, subject to the Neoclassical macroeconomic theory, the literature suggests the comparison of macroeconomic indicators in the sending and receiving country of migrants, respectively; the Background indicates that various determinants explain why the individual decides tomigrate, this study uses the Human Development Index, GDP per capita, unemployment rate,public spending as a percentage of GDP and inflation rate, as determinants to describe the migratory phenomenon. A Pearson correlation matrix is carried out to verify the existing degree of correlation between the dependent and independent variable, carrying out amultiple linear regression model in steps; variables that are not significant are discarded; in this case, it was the Index of Human Development, the rest are admitted taking into accounttheir degree of significance, the participation 84.10% ofthese variables explain the migratoryflow in Ecuador to the United States, period 1990-2020.